ChemInform Abstract: Fe3O4@MgO Nanoparticles as an Efficient Recyclable Catalyst for the Synthesis of Phosphoroamidates via the Atherton—Todd Reaction. Issue 13 (March 2016) - Kaboudin, Babak; Kazemi, Foad; Habibi, Fereshteh
Abstract: A simple, and convenient method for the synthesis of phosphoroamidates via the Atherton—Todd coupling reaction of amines with dialkyl phosphites is reported.